Qualidade de vida relacionada à saúde e adesão ao tratamento de pacientes com câncer de mama e próstata - Viana, Lia Raquel de Carvalho (2020)
Introduction: The experience of breast and prostate cancer and its treatments have significant repercussions on the Health-Related Quality of Life (HRQoL) of individuals, which can reflect negatively on aspects related to therapeutic adherence. Objective: To evaluate HRQoL and treatment adherence in patients with breast and prostate cancer. Method: exploratory, descriptive and cross-sectional study, with a quantitative approach, conducted with 305 patients with breast and prostate cancer at a referral cancer hospital in the State of Paraíba, Brazil, from June to November 2019. For collection of data, a semi-structured instrument was used to obtain data regarding the sociodemographic and clinical profile, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire “core” questionnaire 30 items, the specific module Quality of Life Questionnaire-Breast Cancer and Adherence Determinants Questionnaire-Brazilian Version Scale. Data analysis was performed using descriptive and inferential statistics. The project was approved under opinion number 3,293,768. Results: HRQoL showed high averages in ESG and EF in the groups of patients, and SS obtained worse results in the group with breast cancer undergoing chemotherapy, with emphasis on fatigue, pain, insomnia and financial difficulty. In women, better averages in body image and worse in sexual satisfaction, side effects and breast symptoms were observed. In men, better role performance. The sample showed a medium adherence, highlighting the perceived Support / Severity domain. The correlation between HRQoL and the adherence of patients with prostate cancer showed statistical significance (p≤0.05) between ESG and EF Intentions; Emotional function and Intentions; Insomnia and subjective norms; Financial difficulty and subjective norms. In women, there was statistical significance (p≤0.05) between Role performance and subjective norms; Fatigue and Intentions; Financial difficulty and total adhesion; Sexual desire, sexual satisfaction and perceived support / severity; Breast Symptoms and Intentions. Conclusions: HRQoL directly impacts treatment adherence for patients with breast and prostate cancer.